2021
DOI: 10.1055/s-0041-1726569
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological and Morphometric Evaluation of Microvessel Density in Nodal Non-Hodgkin Lymphoma Using CD34 and CD105

Abstract: Background Expression of angiogenic markers determined by microvessel density (MVD) could be used as a reliable predictor of prognosis and as a potential target for antiangiogenic therapy in different categories of non-Hodgkin lymphoma (NHL). Aims The aim of this study was to evaluate MVD using immunohistochemical methods and computer-assisted quantitative image analysis in nodal NHL patients and compare CD34 and CD105 expression in lymph nodes of NHL patients. Materials and Methods The present study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…We further observed that the restored blood vessels particularly densified and widened in two drug-treated groups, marking the activation of an autoimmune response to recruit pre-existing microvessels and produce neocapillaries ( 43 ). These results were verified again with increased vessel density counts reflected in the CD34 expression in our study, as CD34 is a specific endothelial cell marker for neovascularization ( 35 ). The perfused microcirculation network provides greater tissue perfusion, which satisfies the demand for oxygen delivery and nutritional supply for ulcer reconstruction ( 4 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We further observed that the restored blood vessels particularly densified and widened in two drug-treated groups, marking the activation of an autoimmune response to recruit pre-existing microvessels and produce neocapillaries ( 43 ). These results were verified again with increased vessel density counts reflected in the CD34 expression in our study, as CD34 is a specific endothelial cell marker for neovascularization ( 35 ). The perfused microcirculation network provides greater tissue perfusion, which satisfies the demand for oxygen delivery and nutritional supply for ulcer reconstruction ( 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Some sections for immunohistochemical staining were excluded from the study, as they did not contain ulcer tissue or tissue after ulcer healing. The microvessel density was then assessed through CD34 staining following a previously described protocol ( 35 ). This was followed by hematoxylin and eosin (HE) staining, based on which an inflammation score from 0 to 4 ( 36 ) was determined by two pathologists in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…CD105, better known as endoglin, is a homodimeric transmembrane glycoprotein that highly expressed on activated angiogenic endothelial cells (141). Used as a marker of MVD, CD105 has proven itself as a potent prognostic indicator and a potential target for antiangiogenic therapy and chimeric antigen receptor-based T-cell (CAR-T) immunotherapy in several tumors (142)(143)(144).…”
Section: Proteins In Tumor Tissuementioning
confidence: 99%
“…There is growing evidence of a correlation between the type of vascular condition and the aggressiveness of lymphomas [7,22,23]. To identify signs of transformation and to identify potential biopsy sites, this retrospective study was designed to clarify invasive and indolent Lymphomatous lymph nodes through Ultrasonographic Vascular imaging, which nally impact the selection of treatment programmes.…”
Section: Discussionmentioning
confidence: 99%